Correlation of Salivary Glucose with Serum Glucose in Diabetic Patients - Dawlaty, Dr.Brishna; Sultani, Dr.Abdul Wasi (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background and aim: Composition of Saliva which has similarity with serum has diagnostic value for different diseases. Recently, studying salivary glucose is the major issue for diagnosing Diabetes mellitus. The aim of this study was to determine association between salivary and serum glucose in Diabetes mellitus. Material and Method: This cross sectional study was conducted on 384 diabetic patients who were registered for fasting serum glucose detection in laboratory of IBNE-SENA EMERGENCY HOSPITAL. In this study 269 were female and 115 were male. Glucose in serum and saliva was determined by Glucose oxidase-peroxidase method by semiautomatic analyzer. For detecting association bivariate correlation and linear regression was performed. Results: In this study mean age was 50±0.6 years, Mean fasting salivary glucose and mean fasting serum glucose were 28.19±0.3 and 149.39±3.04mg/dl respectively. Totally 56.3% of samples had serum glucose equal and higher than 126mg/dl. Difference of mean salivary glucose according to age and gender were not significant. In 56.3 % of samples salivary glucose had association with serum glucose but this association was just significant when serum glucose was equal to 126mg/dl or more than it. Conclusion: Fasting Serum glucose more than threshold indicate positive correlation with fasting salivary glucose and according to linear correlation that was found serum glucose could be predictable when fasting salivary glucose was determined but there was no correlation with gender and age.